ARTEMISIA SEEDLINGS QUALITY PRODUCED IN GREENHOUSE UNDER DIFFERENT IRRIGATION SYSTEM AND FERTILIZER DOSES - Marques, Patricia Angelica Alves; Fontinelle, Gabriel Blair; Lima, Alexandre Gibau de; José, Jefferson Vieira; da Rocha, Hermes Soares; Alves, Daniel Soares (IRRIGA, 2017)
ARTEMISIA SEEDLINGS QUALITY PRODUCED IN GREENHOUSE UNDER DIFFERENT IRRIGATION SYSTEM AND FERTILIZER DOSES PATRICIA ANGÉLICA ALVES MARQUES¹; GABRIEL BLAIR FONTINELLE¹; ALEXANDRE GIBAU DE LIMA¹; JEFFERSON VIEIRA JOSÉ2*; HERMES SOARES DA ROCHA3 E DANIEL SOARES ALVES4 [1]Department of Biosystems Engineering, University of Sao Paulo/ESALQ, C.P. 09 – 13418-900 – Piracicaba, SP – Brazil. E-mail: pamarques@usp.br, fontinelleblair@gmail.com, alexandre.gibau.lima@usp.br, 2Department of Agricultural and Environmental Engineering, Institute of Agricultural Sciences and Technology, Federal University of Mato Grosso, C.P. 78735-910 – Rondonópolis, MT – Brazil. E-mail: jfvieira@usp.br 3Institute of Agrarian Sciences, Federal University of the Jequitinhonha and Mucuri Valleys, C.P. 38610-000 – Unaí, MG – Brazil. E-mail: hermes.rocha@ufvjm.edu.br 4Department of Agricultural Engineering, Estate University of Mato Grosso, C.P. 78300-000 – Tanagra da Serra MT – Brazil. E-mail: danielsoares@usp.br 1 ABSTRACT The Artemisia annua L. is a source of essential oils used in perfumery and cosmetics industry, and the yield of oil is affected by the quality of the seedlings used. The present study was carried out in order to evaluate the production of Artemisia annua L. seedlings grown in greenhouse, under two irrigation systems and four levels of commercial fertilizer of high solubility, in a completely randomized design in a 2x4 factorial arrangement and four replications. Germination and growth of roots and shoots seedlings (stems and leaves) were assessed. It was observed at 36 days of sowing (DAS), that plant height was 743% higher on floating system than plants under micro sprinkler system, and that the relationship between root’s and shoot’s dry matter is inversely proportional to the doses of nutrient solution applied. Seedlings showed Dickson quality index greater than 1.3 for all the doses of fertilizer under the floating system. On the other hand, values less than 0.6 were observed for plants under micro sprinkler system. Keywords: seedling production; floating system; medicinal plants irrigation MARQUES, P. A. A; FONTINELLE, G. B.; LIMA, A. G.; JOSÉ, J. V.; ROCHA, H. S.; ALVES, D. S QUALIDADES DE MUDAS DE ARTEMISIA PRODUZIDAS EM CASA DE VEGETAÇÃO SUBMETIDAS A DIFERENTES SISTEMAS DE IRRIGAÇAO E DOSES DE FERTILIZANTES 2 RESUMO A Artemisia annua L. é uma fonte de óleos essenciais utilizados na indústria de perfumaria e cosméticos, e o rendimento do óleo é afetado pela qualidade das mudas. O presente estudo foi realizado para avaliar a produção de mudas de Artemisia annua L. cultivadas em casa de vegetação, sob dois sistemas de irrigação e quatro níveis de fertilizante comercial de alta solubilidade, em um delineamento experimental inteiramente aleatorizado, em esquema fatorial 2x4 e quatro repetições. Foram avaliados a germinação e o crescimento das mudas de raízes e parte aérea (caule e folhas). Foi observado aos 36 dias após a semeadura (DAS) que a altura das plantas era 743% maior no sistema de flutuação do que das plantas sob microaspersão, e que a relação entre massa seca da raiz/massa seca da parte aérea foi inversamente proporcional às doses de solução nutritiva aplicada. As mudas apresentaram índice de qualidade de Dickson superior a 1,3 para todas as doses de fertilizante no sistema flutuante. Por outro lado, valores inferiores a 0,6 foram observados para as plantas sob microaspersão. Palavras-chave: produção de mudas; floating system; irrigação de plantas medicinais